Seoul Conference on International Trade Law: Integration, Harmonization, and Globalization - 1996, Conference (Columbia Journal of Asian Law, 1996)
In July 1995, the Center for Korean Legal Studies at Columbia University School of Law and the American Studies Institute at Seoul National University, in conjunction with support from the Samsung Group, held a conference on issues of international trade law in Seoul, Korea, attended by academics and practitioners from the United States and Korea. The purpose of the Conference was to provide a scholarly forum for discussing some of the salient topics and problems from the perspective of the new world economic order which has risen out of the Uruguay Round trade negotiations and the launching of the World Trade Organization (hereinafter “WTO”). This piece presents slightly edited portions of the Conference discussions, including summaries of two papers presented at the Conference, all related to the issues of international trade law.